Epitaxial III–V/Si Vertical Heterostructures with Hybrid 2D‐Semimetal/Semiconductor Ambipolar and Photoactive Properties. Issue 2 (11th November 2021) - Chen, Lipin; Léger, Yoan; Loget, Gabriel; Piriyev, Mekan; Jadli, Imen; Tricot, Sylvain; Rohel, Tony; Bernard, Rozenn; Beck, Alexandre; Le Pouliquen, Julie; Turban, Pascal; Schieffer, Philippe; et al.
Abstract: Hybrid materials taking advantage of the different physical properties of materials are highly attractive for numerous applications in today's science and technology. Here, it is demonstrated that epitaxial bi‐domain III–V/Si are hybrid structures, composed of bulk photo‐active semiconductors with 2D topological semi‐metallic vertical inclusions, endowed with ambipolar properties. By combining structural, transport, and photoelectrochemical characterizations with first‐principle calculations, it is shown that the bi‐domain III–V/Si materials are able within the same layer to absorb light efficiently, separate laterally the photo‐generated carriers, transfer them to semimetal singularities, and ease extraction of both electrons and holes vertically, leading to efficient carrier collection. Besides, the original topological properties of the 2D semi‐metallic inclusions are also discussed. This comb‐like heterostructure not only merges the superior optical properties of semiconductors with good transport properties of metallic materials, but also combines the high efficiency and tunability afforded by III–V inorganic bulk materials with the flexible management of nano‐scale charge carriers usually offered by blends of organic materials. Physical properties of these novel hybrid heterostructures can be of great interest for energy harvesting, photonic, electronic or computing devices. Abstract : Here, it is demonstrated that epitaxial bi‐domain III–V/Si are hybrid structures, composed of bulk photo‐active semiconductors with 2D topological semi metallic vertical inclusions, endowed with ambipolar properties. Operating III–V/Si photoelectrodes confirm that this hybrid material can by itself photogenerate and laterally separate carriers, which are efficiently extracted afterward from the photoelectric device.